Barium extraction from liquid xenon on a cryoprobe for the nEXO experiment and a nucleon decay search using EXO-200 data - Craycraft, Adam B., author; Fairbank, William M., Jr., advisor; Roberts, Jacob, committee member; Wilson, Robert, committee member; Johnson, Thomas E., committee member (Colorado State University. Libraries, 2019)
Neutrinoless double beta decay (0νββ) is a theorized decay that is beyond the standard model of particle physics. Observation of this decay would establish the Majorana nature of neutrinos and show violation of lepton number. Nucleon decay is another theorized decay that is beyond the standard model of particle physics that would violate baryon number. Observation of baryon number violation has been pursued for sometime in a wide variety of experiments. EXO-200 is an experiment that utilized a time projection chamber (TPC) filled with liquid xenon (LXe) enriched in the isotope xenon-136 to search for 0νββ. In this thesis, an analysis of EXO-200 data in search of evidence for triple-nucleon decays in ¹³⁶Xe is presented. Decay of ¹³⁶Xe to ¹³³Sb and decay to ¹³³Te were the particular decays searched for in this analysis. No evidence for either decay was found. Limits on the lifetimes of these decays were set that exceed all prior limits. The proposed nEXO experiment will be next generation LXe TPC search for 0νββ. In order to eliminate background events that are not associated with two neutrino double beta decay, a technique to tag the barium-136 decay daughter is under development. In this thesis, continued development is presented of a scheme to freeze the barium daughter in a solid xenon sample on the end of a cryoprobe dipped into LXe and subsequently tag it using its fluorescence in the solid matrix.
Keywords: beta decay; neutrinos; nucleon decay; EXO-200; barium; nEXO